Avaliação quimiométrica da influencia da carcinicultura sobre a qualidade da água do Rio da Ribeira/Santa Rita-/PB - Anjos, Aline Emanuela da Silva (2009)
Shrimp farming is now considered an economic activity of major importance in the world and Brazil is among the major producers, with an great potential for cultivation of marine shrimp in the coastal zone, especially in the Northeast. The positive aspects of shrimp farming are undeniable, from the economic and social point of view, but it has caused concern to environmental control agencies of Brazil (IBAMA) due to possible impact on the mangrove ecosystem. However, there is still little information available about the impact of shrimp farming in aquatic ecosystems in our region. This work provides technical and scientific data to support the environmental control agencies and contribute to the development of cultivated areas and their surroundings and to preserve the ecosystem. So a study about the environmental changes in water quality due to the effluent from shrimp farming in a stretch of the Rio da Ribeira, located in Livramento, Santa Rita-PB was done. They were analyzed 288 samples collected at 3 points (Upstream, Downstream and Pond) and 13 parameters were measured in the period of September 2004 to May 2009. For interpretation of the data were applied the chemometric techniques HCA, PCA, Discriminant Analysis (DA) and SIMCA. The results showed no significant differences between the points Upstream (M) and Downstream (J). Therefore, it was showed that shrimp farming has caused no changes in water quality of the environment studied.